Drivers of the Gender Gap in Pensions : Evidence from EU-SILC and the OECD Pension Model - Lis, Maciej; Bonthuis, Boele (World Bank, Washington, DC, 2019)
This paper explores trends and drivers behind the gender gap in pensions (GGP) in Europe, focusing on countries with notionally defined contribution (NDC) schemes: Italy, Latvia, Norway, Poland, and Sweden. Based on current gender gaps on the labor market, the paper relates the progressivity of pension systems and the coverage of child care related spells to the GGP. It shows that NDC countries do not stand out as a group compared to other European countries in terms of pension outcomes for women. Nevertheless, NDC countries differ significantly from one another. Choices of indexation of pensions in payment and survivors’ pension options have a strong impact on genderinequalities. Still, labor market differences are the most important driver of the GGP.